PENGARUH RASIO PROFITABILITAS, RASIO LEVERAGE, RASIO LIKUIDITAS, DAN ECONOMIC VALUE ADDED TERHADAP HARGA SAHAM INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prima Apriwenni, SE., M.Ak., MM., M.Ak; Ir. Tumpal J.R Sitinjak, MM; Viani Vemberia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2011)
This research intended to examine the influence of profitability ratio, leverage ratio, liquidity ratio, and economic value added toward the stock market price in manufacturing industry listed on the Indonesia Stock Exchange. Â This research conducts hypothesis testing of 80 manufacturing companies listed on the Indonesia Stock Exchange during the period of 2007-2009 based on purposive sampling method. This research employs multiple regression analysis tool, validity test-regression model, and classical assumption test. The result shows that among the five financial ratios used as independent variables in this research, only earning per share (EPS) and current ratio (CR) positive and significantly influence the stock market price. This research concludes that EPS and CR positive and significantly affect the stock market price, whereas return on equity (ROE), debt to equity ratio (DER), and economic value added (EVA) do not have any effect towards stock market price. Â Keywords: profitability ratio, leverage ratio, liquidity ratio, economic value added, stock price.